Notes in occurrence and distribution of Lichens in South East Greenland. - Steen Hansen, Eric (Meddelelser om Grønland, 1978)
The present investigation of occurrence and distribution of lichens in South East Greenland is based on a study of 6.000 collections of 155 species of macro- and microlichens collected by the author in 1970 and 1971 in 28 localities situated between Hermods Vig in the Skjoldungen area, c. 63° !at. N., and Mudderbugt in the Kangerdlugssuaq area, c. 68° !at. N. Five of the species, viz. Caloplaca marina (WEDD.) ZAHLBR., Coriscium viride (ACH.) VAIN., Ochrolechia grimmiae LYNGE, Parmeliopsis hyperopta (ACH.) ARN. and Toninia coeruleonigricans (LIGHTF.) TH. FR., are new additions to the lichen flora of East Greenland. Previous lichenological research work in South East Greenland is surveyed in an introductory chapter. The collected species of lichens are grouped on the basis of their ecological preferences, and an account is given of some characteristic features of the lichen vegetation at the investigated localities within the Skjoldungen-, the Angmagssalikand the Kangerdlugssuaq area. Distribution maps of four species, viz. Cladonia cyanipes (SOMM.) NYL., Lecanora straminea (WAHLENB.) AcH., Parmeliopsis ambigua (WuLF.) NYL. and Peltigera venosa (L.) BAUMG., have been compiled.